Spectral and spectral element methods for fractional ordinary and partial differential equations - Zayernouri, Mohsen; Wang, Li-Lian; Shen, Jie; Karniadakis, George 1959- (Cambridge monographs on applied and computational mathematics, 2024)
This comprehensive introduction to global 9781108490993 for fractional differential equations from leaders of this emerging field is designed to be accessible to graduate students and researchers across math, science, and engineering. The book begins by covering the foundational fractional calculus concepts needed to understand and model anomalous transport phenomena. The authors proceed to introduce a series of new spectral theories and new families of orthogonal and log orthogonal functions, then present corresponding spectral and spectral element methods for fractional differential equations. The book also covers the fractional Laplacian in unbounded and bounded domains and major developments in time-integration of fractional models. It ends by sampling the wide variety of real-world applications of fractional modeling, including concentration transport in surface/subsurface dynamics, complex rheology and material damage, and fluid turbulence and geostrophic transport